The relationship between knowledge, attitude, and practice towards snacking habits with dental caries status among children aged 8–11 years at Ketabang 1 Public Elementary School, Surabaya - Dini Setyowati; Nabila Adine Putri; Intan Aprillia Putri Erinda; Annisa Tri Maharani; Andre Amin Supatra; Nur Hikmatus Sa’adah; Amanda Ayu Aprilia; Jasmine Dharmarani Saputra; Sella Pujaya Wahyu Aifma; Fanya Suryanti; Tengku Natasha Eleena binti Tengku Ahmad Noor (Indonesian Journal of Dental Medicine, 2026)
Background: Dental caries is a chronic infectious disease caused by bacterial activity that demineralizes tooth enamel and dentin. According to the 2018 Indonesian Basic Health Research (Riskesdas), 67.3% of school-aged children experience oral health problems, with dental caries being the most prevalent (88.8%). Purpose: This study aimed to analyze the relationship between knowledge, attitude, and practice towards snacking behavior with dental caries status among children aged 8–11 years at Ketabang 1 Public Elementary School, Surabaya, in 2025. Methods: This observational analytic study used a cross-sectional design involving 85 students selected through cluster random sampling. Data on knowledge, attitude, and snacking behavior were collected using a structured questionnaire, while dental caries status was clinically examined using the DMFT and PUFA indices. Statistical analyses included the Chi-square test, Independent T-test, and Mann–Whitney test with a significance level of p < 0.05. Results: The mean DMFT scores ranged from 2.53 ± 1.37 to 4.65 ± 2.12, and the mean PUFA ranged from 0.20 ± 0.37 to 0.58 ± 0.67, indicating moderate to high caries prevalence. Chi-square analysis showed a significant relationship between knowledge (p = 0.000) and practice (p = 0.003) with dental caries status, while attitude showed no significant correlation (p = 0.943. Conclusion: Knowledge and snacking behavior are significantly associated with dental caries status among school-aged children, whereas attitude shows no significant relationship. Strengthening oral health education and promoting healthy snacking habits are crucial to reducing caries incidence in elementary school children.